Transport organization and economic development of an European peripherical region: the case of Sicily - Vittorio Ruggiero; Luigi Scrofani (European Regional Science Association (ERSA), 2003)
Transport and communication networks are some of the most important factors which influence the socio-economic development, and particularly the tourist sector, of Sicily, a peripherical region by comparison with the European central areas. The most recent changes in the transport sector are: a) the creation of integrated trans-national networks, based on specific systems such as the inter-modality transport one and the hub and spoke one. b) the solution of the conflicts between transport development and environmental impact. These changes lead to the creation of global national and regional logistic networks, which increased the competition and efficiency of states/regions/local economic systems. In this paper the authors will analyse how Sicily wants to face these transformations in order to change its economic functions in the Euro-Mediterranean area. On the other side they will take in consideration how the principal choices of European Union influence the projects of Sicilian transport Plans and if Sicilian actors are able to use the European financial resources available in transport sector.
Keywords: 330